Incidence of major insect pests on sweet gourd germplasm - Afroz, M; Amin, MR; Miah, MRU; Hossain, MM (Bangladesh Journal of Agricultural Research, 2020)
Abundance of the major insect pests viz., red pumpkin beetle, epilachna beetle and fruit fly on twelve sweet gourd germplasms namely BD 264, BD 265, BD 266, BD 268, BD 269, BD 274, BD 275, BD 277, BARI Mistikumra 1, BARI Mistikumra 2, Gazipur Local Line and China line was studied in the experimental field of the Department of Entomology, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh during July 2018 to June 2019. The mean number of red pumpkin was the highest (2.3 adults/ 3 leaves) during 4th week of December and the lowest (0.7 adults/ 3 leaves) during 4th week of March. The mean number of grub (6.5 grubs/3 leaves) and adult (2.3 adults/ 3 leaves) of epilachna beetle were the highest during 2nd week of March and 4th week of February, respectively. The mean number of fruit fly was found the lowest (1.0 adults plant-1) during 5th week of January and the highest (2.5 adults plant-1) during 4th week of February. BARI Mistikumra 1, BARI Mistikumra 2 and China Line provided the lowest yield ranged from 4.8 ± 5.3 to 7.4 ± 0.5 t ha-1 and the remaining germplasms showed statistically similar yield. Bangladesh J. Agril. Res. 44(4): 621-630, December 2019